Continuing Formal Education For Nurses: Exploring The Experiences Of Non - Professional Nurses In The Greater Accra Region - Agyepong, E.B. (University of Ghana, 2017)
Continuing formal education is essential to the growth of the nursing profession due to the dynamic environment of the health industry. Nurses after their initial training received at school, have the opportunity to engage in continuing formal education. The study sought to have an in - depth exploration of the perceptions, motivators, barriers and measures to enhance the continuing formal education of non - professional nurses. The qualitative descriptive design was employed and the purposive sampling technique used to recruit twenty - three non - professional nurses from Pantang Hospital in the Greater Accra Region. The thematic content analysis was used in analysing the data. Four main themes that guided the study were the perception of continuing formal education, motivation for continuing formal education, barriers to continuing formal education and measures to enhance continuing formal education. The findings of the study showed that non - professional nurses have a positive perception about continuing formal education. Motivating factors that encouraged non - professional nurses’ return to school include self - determination and age, low academic qualification and practising outside one’s job description. Barriers to continuing formal education originated from the personal situation of non - professional nurses, educational institutions, the non - professional nurse’s disposition towards school as well as employers and management of healthcare facilities within which non - professional nurses work. The measures to enhance continuing formal education of non - professional nurses include clear educational policies on education and the development of educational programmes to meet the needs of non - professional nurses. The study recommended that continuing formal education should be considered as a collective responsibility of all stakeholders responsible for the continuing formal education of non - professional nurses. Appropriate measures are therefore required by stakeholders to promote the continuing formal education of non -professional nurses.
Thesis (MPhil)
Keywords: Continuing Formal Education; Nurses; Non - Professional Nurses; Greater Accra Region; Ghana